Large-Scale Triaxial Tests on Dilatancy Characteristics of Lean Cemented Sand and Gravel - Yu, Hang; Shen, Xue-mei; Ye, Yu-chen; Yang, Jie; Zhu, Chen-hui (Frontiers in Earth Science, 2021)
The dilatancy equation, which describes the plastic strain increment ratio and its dependence on the stress state, is an important component of the elastoplastic constitutive model of geotechnical materials. The dilatancy properties of lean cemented sand and gravel (LCSG) materials are usually expressed directly by the dilatancy equation of rockfill materials, but the accuracy of the results is in error with that of the real value. In this study, a series of triaxial compression tests, equiaxial loading and unloading tests, and triaxial loading and unloading tests are conducted under different cement contents and confining pressures. The results reveal that hysteretic loops appear in the stress–strain curves of the shear triaxial tests and isotropic triaxial tests in the unloading and reloading path under different confining pressures and that the elastic strain is an important component of the total strain. The hysteretic loop size increases with an increase in the stress level or consolidation stress, whereas the shape remains unchanged. Furthermore, with an increase in the cement content, the dilatancy value determined by the total volume strain increment ratio becomes smaller than that determined by the plastic strain increment ratio, and the influence of the elastic deformation cannot be ignored. Thus, in practical engineering scenarios, especially in the calculation of LCSG dam structures, the dilatancy equation of LCSG materials should be expressed by the plastic strain increment ratio.